Effects of Polymethoxyflavonoids on Bone Loss Induced by Estrogen Deficiency and by LPS-Dependent Inflammation in Mice - Shigeru Matsumoto; Tsukasa Tominari; Chiho Matsumoto; Shosei Yoshinouchi; Ryota Ichimaru; Kenta Watanabe; Michiko Hirata; Florian M. W. Grundler; Chisato Miyaura; Masaki Inada (MDPI AG, 2018)
Polymethoxyflavonoids (PMFs) are a family of the natural compounds that mainly compise nobiletin, tangeretin, heptamethoxyflavone (HMF), and tetramethoxyflavone (TMF) in citrus fruits. PMFs have shown various biological functions, including anti-oxidative effects. We previously showed that nobiletin, tangeretin, and HMF all inhibited interleukin (IL)-1-mediated osteoclast differentiation via the inhibition of prostaglandin E2 synthesis. In this study, we created an original mixture of PMFs (nobiletin, tangeretin, HMF, and TMF) and examined whether or not PMFs exhibit co-operative inhibitory effects on osteoclastogenesis and bone resorption. In a coculture of bone marrow cells and osteoblasts, PMFs dose-dependently inhibited IL-1-induced osteoclast differentiation and bone resorption. The optimum concentration of PMFs was lower than that of nobiletin alone in the suppression of osteoclast differentiation, suggesting that the potency of PMFs was stronger than that of nobiletin in vitro. The oral administration of PMFs recovered the femoral bone loss induced by estrogen deficiency in ovariectomized mice. We further tested the effects of PMFs on lipopolysaccharide-induced bone resorption in mouse alveolar bone. In an ex vivo experimental model for periodontitis, PMFs significantly suppressed the bone-resorbing activity in organ cultures of mouse alveolar bone. These results indicate that a mixture of purified nobiletin, tangeretin, HMF, and TMF exhibits a co-operative inhibitory effect for the protection against bone loss in a mouse model of bone disease, suggesting that PMFs may be potential candidates for the prevention of bone resorption diseases, such as osteoporosis and periodontitis.